Effect of Vitamin B12 on Functional Recovery and Histopathologic Changes of Tibial Nerve-Crushed Rats - Tamaddonfard, E.; Farshid, A. A.; Samadi, F.; Eghdami, K. (Drug Research, 2014)
Recent studies have suggested a neuroprotective effect for vitamin B12. The present study investigated the effects of vitamin B12, diclofenac and celecoxib in separate and combined treatments on functional recovery of crushed tibial nerve in rats. In ketamine plus xylazin anesthetized rats, right tibial nerve was crushed using a small hemoatatic forceps. Footprints were recorded 1 day before and on days 7, 14 and 21 after induction of nerve injury. Tibial functional index (TFI) was used to evaluate the recovery of tibial nerve function. Histological changes of tibial nerve were investigated by light microscopy. The recovery of TFI values were significantly accelerated with 10 consecutive days treatments with 0.1 and 0.5 mg/kg of vitamin B12, 5 mg/kg of diclofenac and 1 and 5 mg/kg of celecoxib. The severity of Wallerian degeneration was reduced by above-mentioned doses of vitamin B12, diclofenac and celecoxib. Documented effects were observed when 0.1 mg/kg of vitamin B12 was concurrently used with 1 mg/kg of diclofenac and or 0.2 mg/kg of celecoxib. In the present study, vitamin B12, celecoxib and diclofenac (at a high dose) showed neuroprotective effects. Inhibition of cyclooxygenase (COX) 1 and 2 pathways may be involved in neuroprotective effect of vitamin B12.
Keywords: vitamin B12; cyclooxygenase; neuroprotection; peripheral nerve; rats